Efektivitas Penerapan Upaya Hukum Kasasi dalam Perkara Perdata - Febriansyah Maradi Putra; Abdul Fatah Baskoro; Tegar Harbriyana Putra (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The cassation legal effort has a high urgency in the Indonesian civil justice system as a corrective mechanism for errors in the application of law and an instrument to ensure uniformity of national law. The relevance of this topic is increasing along with the large number of cassation cases submitted to the Supreme Court (MA) and has the potential to hamper the legal function of the highest judicial institution. This study aims to analyze the effectiveness of the application of cassation in civil cases and identify various obstacles that affect its implementation. This study uses a normative legal method with a regulatory approach and case studies supported by a literature study of laws and regulations, court decisions, and appropriate legal literature. The research findings indicate that the effectiveness of cassation is hampered by a combination of internal factors, such as excessive caseloads and limitations of the MA information system, as well as external factors such as weak legal understanding of the parties, declining quality of previous court decisions, and misuse of cassation as a litigation strategy. This study concludes that structural reform and increased capacity of judicial actors are needed, as well as strengthening of civil procedural law norms in order to clarify the role of cassation as a tester of the application of law, not a forum for objections to facts. This study contributes to the discourse on judicial reform and opens up opportunities for further research with empirical and comparative legal system approaches.